Podcasting as a Specific Feature of Radio Production - Stachyra, Grażyna (Media - Culture - Social Communication, 2019)
This paper aims to analyze a podcast’s features which derive from podcasting technology and to describe its relations to radio broadcasting. While some researchers treat podcasting as an alternative to broadcasting, others situate it in the field of radio broadcasting. This study focuses on the similarities and differences between podcasting and radio modus.